SELF REGULATED LEARNING (SRL) DITINJAU DARI JENIS KELAMIN MAHASISWA FAKULTAS TEOLOGI UNIVERSITAS KRISTEN SATYA WACANA - Sepriadi Antoni; Sutarto Wijono; Arthur Huwae (Journal of Innovation Research and Knowledge, 2026)
Background: Self-Regulated Learning (SRL) is an essential competency that enables students to manage, monitor, and evaluate their own learning processes to achieve academic goals. Although gender has been identified as one of the factors influencing SRL, previous studies have produced inconsistent findings. This study aimed to examine differences in Self-Regulated Learning based on gender among students of the Faculty of Theology at Satya Wacana Christian University. Methods: This study employed a quantitative comparative design involving 97 undergraduate students from the 2022 and 2023 cohorts. Participants were selected using purposive sampling. Data were collected through an online questionnaire using a Self-Regulated Learning scale developed based on Schunk and Zimmerman’s theory, consisting of 24 items covering six dimensions: self-efficacy and goal setting, learning strategies, time management, self-observation, environmental structuring, and selective help-seeking. The instrument demonstrated excellent reliability (Cronbach’s Alpha = 0.915). Since the data were not normally distributed, the Mann–Whitney U test was applied to examine gender differences. Results: The findings revealed no significant difference in Self-Regulated Learning between male and female students (Asymp. Sig. = 0.148, p > 0.05). Both groups demonstrated moderate levels of Self-Regulated Learning, with mean scores of 72 for male students and 71 for female students. These findings indicate that gender is not a determining factor in students' self-regulated learning abilities. Conclusion: Self-Regulated Learning among Theology students does not significantly differ by gender. Instead, SRL appears to be more strongly influenced by personal characteristics, learning behaviors, and supportive learning environments than by biological sex. Therefore, universities should promote learning strategies and academic support systems that enhance students’ self-regulated learning regardless of gender.